Hepatitis C Virus Infection and Renal Disorders (Journal of Renal and Hepatic Disorders, 2019)
Hepatitis C virus (HCV) infection is frequently associated with extrahepatic disorders, among which renal diseases are frequent. This article highlights the most frequent HCV-associated renal disorders, the impact of HCV infection on chronic renal disease and renal transplantation, and the role of current direct-acting antiviral therapies. HCV is associated with membranoproliferative glomerulonephritis, acceleration of end-stage renal diseases in patients with glomerulopathies, and a higher risk of death in patients affected by chronic kidney disease. Before the introduction of direct-acting antiviral drugs as treatment modality, renal transplantation was a challenging clinical problem because the drugs available until 2011 obtained a poor sustained virologic response, had several side effects, and caused acute rejection when used after transplantation. The knowledge of the viral structure and its replication allowed the discovery of new classes of direct-acting antiviral drugs that revolutionized this scenario. These new drugs are comparatively more effective and safer. Accumulating evidence suggests that it is possible to cure HCV-related glomerulonephritis, and obtain a sustained virologic response in patients with renal failure, or on dialysis, before commencing transplantation. Finally, it became possible to transplant HCV-positive kidneys into HCV-positive or HCV-negative recipients.
Keywords: direct antiviral agents; extrahepatic disorders; hepatitis C virus; membranoproliferative glomerulonephritis; mixed cryoglobulinemia